A three-dimensional (time, wavelength and intensity) functioning fluorescent probe for the selective recognition/discrimination of Cu2+, Hg2+, Fe3+ and F− ions. Issue 11 (16th February 2018) - Ruan, Qin; Mu, Lan; Zeng, Xi; Zhao, Jiang-Lin; Zeng, Li; Chen, Zhen-Min; Yang, Cai; Wei, Gang; Redshaw, Carl
Abstract : A new probe for the selective recognition/discrimination of Cu 2+, Hg 2+, Fe 3+ and F − ions by measuring their response time, wavelength and fluorescence intensity. Abstract : We have strategically incorporated three different fluorophores at tren to construct a multi-energy donor/acceptor "smart" probeL . This probe operates by using three-dimensional scales (response time, wavelength and fluorescence intensity) which allows for the selective recognition and discrimination of the Cu 2+, Hg 2+, Fe 3+ and F − ions.